Gramaticalização do verbo seguir em notícias da imprensa cearense - Rolim, Renata Alves (2024)
Based on the functionalist framework, more precisely the North American approach (Hopper, 1991; Hopper and Traugott, 1991; Bybee, 1994), the general objective of this research is to analyze the process of linguistic change of the verb seguir, from the point of view of grammaticalization, in the textual context of the Notícia genre, from the Ceará press. At the same time, our specific objectives include describing and analyzing this process, investigating linguistic and extralinguistic conditions, while looking for a relationship between syntax, semantics and pragmatics in establishing the multifunctions of this verb, as well as mapping the number of occurrences for proper analysis and comparison, in addition to looking for aspectual patterns in seguir in the syntactic constructions in which it appears as a linking verb and auxiliary verb. To do this, we checked the functions performed by seguir, whether full or not, in order to identify a continuum (Hopper and Traugott, 1993); in addition, we analysed the behaviour of these new functionalities, recognizing in them the principles assumed by Hopper (1991): stratification, divergence, specialization, persistence and decategorization. Our corpus was made up of 196 news items published between 2018 and 2024, from two newspapers considered to have the greatest reach in the state of Ceará: Diário do Nordeste and Ceará News 7, both in virtual format, 96 items from the former and 100 from the latter. According to our research, we saw the progress of the grammaticalization of seguir, a verb whose meaning changed from movement to time, also gaining new functions: from full to linking verb and then auxiliary, thus losing its lexical meaning in many contexts and taking on a grammatical value. Our analysis considered conditions such as syntactic construction, sense of use, aspectuality, semantic and thematic traits of the news items, variables whose considerations led us to frequency figures that conditioned our conclusions about the grammaticalization of the item. The study allowed us to list which new syntactic functions the verb has taken on, whether it is a linking verb or an auxiliary verb, as well as in which types of constructions it has started to appear, whether associated with adverbial, nominal or adjectival phrases or verbs in the gerund, constituting or not an auxiliary. As for the extension of meaning, the verb under study, giving way to temporal meaning, took on meanings such as continue and remain, which appeared more frequently, compared to other less usual meanings, such as accept, advance and agree. At the same time, we saw the semantic abstraction of this verb, which became less concrete in most contexts of use, while losing the canonical idea of movement. When it comes to the aspectual category, we noticed that the periphrases of seguir mark, in all the cases recorded, the notion of indeterminate, durative, started or unfinished and cursive. Finally, with regard to pragmatic choices, the themes in which seguir appeared were diverse, with varying frequency, depending on the newspaper, concentrating its constancy on the subject of sport, in the newspaper Diário do Nordeste, and on the subject of politics, in Ceará News 7.